2022
DOI: 10.1007/s12010-022-04095-0
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Polymer Precursor 12-Oxododecenoic Acid Utilizing Recombinant Papaya Hydroperoxide Lyase in an Enzyme Cascade

Abstract: Hydroperoxide lyases (HPLs) catalyze the splitting of 13S-hydroperoxyoctadecadienoic acid (13S-HPODE) into the green note flavor hexanal and 12-oxo-9(Z)-dodecenoic acid, which is not yet used industrially. Here, HPL from Carica papaya (HPLCP) was cloned and functionally expressed in Escherichia coli to investigate synthesis of 12-oxo-9(Z)-dodecenoic acid in detail. To improve the low catalytic activity of full-length HPLCP, the hydrophobic, non-conserved N-terminal sequence was deleted. This enhanced enzyme ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(21 citation statements)
references
References 47 publications
0
21
0
Order By: Relevance
“…However, the three-enzyme cascade with LOX-1 resulted in a much lower conversion. In our previous study, we showed that the HPL reaction is significantly faster than the LOX reaction (Coenen et al 2022). Hence, the slow formation of 13S-HPODE could be the cause of the lower overall activity observed in the coupled three-enzyme system.…”
Section: Discussionmentioning
confidence: 96%
See 4 more Smart Citations
“…However, the three-enzyme cascade with LOX-1 resulted in a much lower conversion. In our previous study, we showed that the HPL reaction is significantly faster than the LOX reaction (Coenen et al 2022). Hence, the slow formation of 13S-HPODE could be the cause of the lower overall activity observed in the coupled three-enzyme system.…”
Section: Discussionmentioning
confidence: 96%
“…12-Oxo-9( Z )-dodecenoic acid was dissolved in ethanol and frozen at − 80 °C until further use. The amount and purity of 12-oxo-9( Z )-dodecenoic acid were confirmed by GC analysis as described previously (Coenen et al 2022 ). The remaining hexanal concentration was less than 1.5% compared to 12-oxo-9( Z )-dodecenoic acid.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations